2012
DOI: 10.1097/tp.0b013e318248375a
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Intravenous or Oral Iron for Posttransplant Anemia in Kidney Transplantation

Abstract: We conclude that a single dose of IV iron did not result in more rapid resolution of anemia compared with PO iron. Both IV and PO iron are safe and effective in the management of posttransplant anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 11 publications
0
47
0
Order By: Relevance
“…TSAT and serum ferritin level are used as iron metabolism markers for grafts as in CKD patients, although their effectiveness in an inflammatory environment due to infections and rejection episodes is questioned [274,275]. One report showed that there was no significant difference between the efficacy of oral and intravenous iron supplementation for PTA patients [276]. For details about administration methods, readers should refer to Chapter 4 ("Evaluation of iron status and iron therapy") of these guidelines.…”
Section: Rationalementioning
confidence: 99%
“…TSAT and serum ferritin level are used as iron metabolism markers for grafts as in CKD patients, although their effectiveness in an inflammatory environment due to infections and rejection episodes is questioned [274,275]. One report showed that there was no significant difference between the efficacy of oral and intravenous iron supplementation for PTA patients [276]. For details about administration methods, readers should refer to Chapter 4 ("Evaluation of iron status and iron therapy") of these guidelines.…”
Section: Rationalementioning
confidence: 99%
“…A recent randomized controlled trial of iron supplementation found no difference between per oral and intravenous route with regard to restoration of Hb‐levels to >11 g/dl postoperatively, but long term iron supplementation has not been investigated in controlled trials [73]. Except for a recent trial on Hb‐correction by ESA therapy [85], there is no randomized controlled study of sufficient size that allows definitive answers to questions as: when to treat, how to treat and to which levels, Hb‐values should be raised.…”
mentioning
confidence: 99%
“…With impaired iron uptake from the gastrointestinal tract (in anemia of chronic disease (ACD) [3] or after bariatric surgery), suboptimal responsiveness to exogenous erythropoietin (in chronic renal failure) [4], in patients with cancer receiving chemotherapy [5], or when oral iron is poorly tolerated, IV iron therapy is the preferred mode of repletion [2,5]. Although effective in increasing hemoglobin [6][7][8][9][10], the relative safety of the available IV iron preparations is not well documented. We examined the comparative safety of IV iron formulations used at hospitals associated with our institution.…”
mentioning
confidence: 99%